2013
DOI: 10.1111/codi.12333
|View full text |Cite
|
Sign up to set email alerts
|

Live anatomy of the perineal body in patients with third‐degree rectocele

Abstract: In women with low rectocele, the perineal body appears to be divided into two parts, severely displaced behind the ischial tuberosities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Their use has further limitations as they may have suffered from topographical distortion due to fixation and loss of muscle tone. Other researchers have examined the PB by thin-slice magnetic resonance imaging [18] or by in vivo surgical observations [19][20][21]. Wagenlehner et al [19,20] have shown that the PB could be divided into two parts, connected via a central tendon, but it was not possible to examine the two parts of the PB in the present study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Their use has further limitations as they may have suffered from topographical distortion due to fixation and loss of muscle tone. Other researchers have examined the PB by thin-slice magnetic resonance imaging [18] or by in vivo surgical observations [19][20][21]. Wagenlehner et al [19,20] have shown that the PB could be divided into two parts, connected via a central tendon, but it was not possible to examine the two parts of the PB in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…Wagenlehner et al . have shown that the PB could be divided into two parts, connected via a central tendon, but it was not possible to examine the two parts of the PB in the present study. The functional role of the PB has to be explored in vivo .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…• Level IV : at the outer level, the perineal muscles (bulbospongiosus, ischiocavernosus, and superficial transverse perineii muscles), the perineal body, the distal urethra and the middle and inferior third of the anal canal are visualized. The anterior‐posterior diameter of the urogenital hiatus (UGH), corresponding to the SP‐perineal body distance, can be determined …”
Section: Section 5: Imagingmentioning
confidence: 99%
“…According to DeLancey [3], this structure plays a critical role in Level III support. Damage to the PB, which frequently occurs during vaginal childbirth, is associated with pelvic organ prolapse [34][35][36][37][38]. Many studies have described the anatomy of the PB, but there is still considerable variation regarding its attachments and relationships [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%